2018
DOI: 10.1111/myc.12740
|View full text |Cite
|
Sign up to set email alerts
|

Candiduria in kidney transplant recipients: Is antifungal therapy useful?

Abstract: A French single-centre retrospective study between 2010 and 2014 was undertaken to assess candiduria's incidence in kidney transplant recipients (KTR), and the use and impact of antifungal treatment on outcome. Candiduria was defined as a urine culture with ≥10 cfu/mL of Candida species. Candiduria clearance, severe complications and death rates were estimated by Kaplan-Meier methods and the effect of treatment by Cox models. 52/1223 (4.3%) KTR had ≥1 episode of candiduria, 42 (81%) were females, 18 (35%) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“… 19 Similarly, in an observational study that assessed candiduria incidence and treatment outcomes in 1223 patients with kidney and kidney-pancreas transplant, Denis and colleagues identified C. glabrata as the most common responsible organism. 25 Medical therapy had no significant effect on the fungal clearance rate or the development of serious complications, including death, that were mostly encountered in the first 2 weeks post-transplantation. Furthermore, Mai et al and Rodrigues et al reported cases where the IFI led to fungal arteritis and mycotic aneurysm and, in some cases, resulted in massive bleeding and death.…”
Section: Discussionmentioning
confidence: 93%
“… 19 Similarly, in an observational study that assessed candiduria incidence and treatment outcomes in 1223 patients with kidney and kidney-pancreas transplant, Denis and colleagues identified C. glabrata as the most common responsible organism. 25 Medical therapy had no significant effect on the fungal clearance rate or the development of serious complications, including death, that were mostly encountered in the first 2 weeks post-transplantation. Furthermore, Mai et al and Rodrigues et al reported cases where the IFI led to fungal arteritis and mycotic aneurysm and, in some cases, resulted in massive bleeding and death.…”
Section: Discussionmentioning
confidence: 93%
“…We have to bear in mind that in many cases, the presence of Candida in laboratory results could be the result of colonization or contamination and not infection. Several studies have demonstrated that antifungal treatment in KT patients with asymptomatic candiduria does not increase the clearance of candiduria or decrease the incidence of recurrences, suggesting that antifungal therapy is not associated with clinical benefit in these cases [27].…”
Section: Discussionmentioning
confidence: 99%
“…Candiduria is common following KT but is rarely of clinical significance with a median time to occurrence of 25 days, likely to be diabetic, female patients who have experienced significant prior antimicrobial exposure. Antifungal therapy in patients with asymptomatic candiduria has been shown to have no impact on the risk of recurrence, urinary clearance, or the development of severe complications [2,[71][72][73]. Given the low incidence of infection, and the lack of impact of treatment of asymptomatic candiduria, both the Infectious Diseases Society of America (IDSA) and the American Society of Transplantation Infectious Diseases Community of Practice do not recommend antifungal therapy for asymptomatic candiduria [28,74] (Table 2).…”
Section: Kidneymentioning
confidence: 99%